Enamel susceptibility to red wine staining after 35% hydrogen peroxide bleaching - Berger,Sandrine Bittencourt (2008)
Concern has been expressed regarding the staining of enamel surface by different beverages after bleaching. This study investigated the influence of 35% hydrogen peroxide bleaching agents on enamel surface stained with wine after whitening treatments. Flat and polished bovine enamel surfaces were submitted to two commercially available 35% hydrogen peroxide bleaching agents or kept in 100% humidity, as a control group (n = 10). Specimens of all groups were immersed in red wine for 48 h at 37°C, immediately, 24 h or 1 week after treatments. All specimens were ground into powder and prepared for the spectrophotometric analysis. Data were subjected to two-way analysis of variance and Fisher's PLSD test at 5% significance level. The amount of wine pigments uptake by enamel submitted to bleaching treatments was statistically higher than that of control group, independently of the evaluation time. Results suggested that wine staining susceptibility was increased by bleaching treatments.